The Development of a Reading Literacy Ability Test Refers on Problem-Based Biology Learning for High School Students - Ainun Hidayah; Saiful Ridlo (Journal of Biology Education, 2023)
Reading literacy is a prerequisite for achieving 21st century skills. To measure students' reading literacy skills, the Indonesian Ministry of Education and Culture released a Minimum Competency Assessment program known as AKM. This study aims to develop a reading literacy test instrument refers on Problem-Based biology learning for high school students. The test was developed using references from the AKM test model. The type of research used is Research and Development (R&D) with a 4-D model. In this study, the data collected were qualitative data and quantitative data. The qualitative data is the design result of a reading literacy test. The quantitative data includes the validity of the content of the instrument, the characteristics of the question items, the implementation of Problem-Based biology learning, and the level of student literacy ability. The data is analyzed descriptively using a variety of appropriate criteria according to the type of data collected. The reading literacy ability test refers on Problem-Based biology learning contains questions in the form of multiple choice (6 items), complex multiple choice (12 items), matching (3 items), short answer question (2 items) and essay (7 items). The question items are arranged with the content of the informational text and the context of the scientific text on the excretory system material. The validity rate is very valid (93.14%). The test questions have a "medium" difficulty level with a P value of 0.671. The differentiating index of the question item is included in the "good" criteria with a value of Rpbis 0.380. The reliability of the question item is very high (Alpha 0.854). The functioning of the choices is categorized as good. The percentage of implementation the Problem-Based biology learning is very high (100%). The reading literacy level of class XI students of Godong 1 Public SHS is dominated by the proficient level (54%) while class XI students of Semarang 12 Public SHS are dominated by an advanced level (46%). Based on the results of the research, it can be concluded that the reading literacy test refers on Problem-Based biology learning developed is very valid to be used in measuring high school students' literacy ability.